2022
DOI: 10.1002/alz.12834
|View full text |Cite
|
Sign up to set email alerts
|

Herpes simplex virus alters Alzheimer's disease biomarkers ‐ A hypothesis paper

Abstract: Introduction: Human herpes simplex virus 1 (HSV1) is discussed to induce amyloidβ (Aβ) accumulation and neurofibrillary tangles of hyperphosphorylated tau (pTau) in Alzheimer's disease (AD) in cell culture and animal models. Aβ appears to be virostatic. We investigated the association between intrathecal antibodies against HSV or cytomegalovirus (CMV) and cerebrospinal fluid (CSF) AD biomarkers.Methods: Aβ 42 /Aβ 40 ratio, pTau, and tTau were measured in CSF of 117 patients with early AD positive for amyloid p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 71 publications
0
6
0
Order By: Relevance
“…Using cell culture and animal models, we explore how human herpes simplex virus 1 (HSV1) causes amyloid-β (Aβ) buildup and neurofibrillary tangles of hyperphosphorylated tau (pTau) in AD. A seems to have a virostatic effect ( 70 ).…”
Section: Environmental Risk Factorsmentioning
confidence: 99%
“…Using cell culture and animal models, we explore how human herpes simplex virus 1 (HSV1) causes amyloid-β (Aβ) buildup and neurofibrillary tangles of hyperphosphorylated tau (pTau) in AD. A seems to have a virostatic effect ( 70 ).…”
Section: Environmental Risk Factorsmentioning
confidence: 99%
“…Some studies also suggested that the aggregation of pTau may be induced by infections, among other factors ( Lee et al, 2022 ; Sathler et al, 2022 ; Shen et al, 2022 ; Tang et al, 2022 ). The involvement of infections in AD is an emerging field of AD research, and the literature on the factors that may influence both vulnerability to infections and neurodegeneration is increasing ( Yashin et al, 2018 ; Yong et al, 2021 ; Cairns, Itzhaki and Kaplan, 2022 ; Mancuso et al, 2022 ; Nuovo et al, 2022 ; Piekut et al, 2022 ; Sathler et al, 2022 ; Tang et al, 2022 ; Goldhardt et al, 2023 ; Ukraintseva et al, 2023 ; Popov et al, 2024 ). Nectin-2 (Nectin cell adhesion molecule 2) is a membrane component of adherens junctions that serves as an entry point for certain herpesviruses and may mediate response to the viral infection ( Ogawa et al, 2022 ; Goldhardt et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%
“…The involvement of infections in AD is an emerging field of AD research, and the literature on the factors that may influence both vulnerability to infections and neurodegeneration is increasing ( Yashin et al, 2018 ; Yong et al, 2021 ; Cairns, Itzhaki and Kaplan, 2022 ; Mancuso et al, 2022 ; Nuovo et al, 2022 ; Piekut et al, 2022 ; Sathler et al, 2022 ; Tang et al, 2022 ; Goldhardt et al, 2023 ; Ukraintseva et al, 2023 ; Popov et al, 2024 ). Nectin-2 (Nectin cell adhesion molecule 2) is a membrane component of adherens junctions that serves as an entry point for certain herpesviruses and may mediate response to the viral infection ( Ogawa et al, 2022 ; Goldhardt et al, 2023 ). The single nucleotide polymorphism (SNP) rs6859 of the NECTIN2 gene was highly significantly associated with AD risk in observational human data ( Yashin et al, 2018 ; Mizutani et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Reactivation of latent herpes virus infection has been associated to Alzheimer’s disease (AD) even though the molecular mechanisms of this connection remains unknown (Eimer et al, 2018; Itzhaki et al, 1997; Lovheim et al, 2015; Wozniak et al, 2009). Recently, a positive association of HSV-1 antibodies to increased levels of phosphorylated tau in CSF of AD patients was demonstrated (Goldhardt et al, 2022).…”
Section: Introductionmentioning
confidence: 99%